Tribulations Confronted By Women In The Hospitality Industry (PUSA Journal of Hospitality and Applied Sciences, 2016)
Background: Women constitute an important labour force in all the countries. Nearly 1/3rd of our  labour force [32%] consists of women. Working women constitute 16.43% of the female population  of the country. The main problem with these female workers is that they are harassed in work  place in different ways. Objective: Unveil the challenges, problems and difficulties confronted  by women at their work place as well as at their home due to their profession. Method: The  study was conducted on seventy eight women working in the hospitality industry and data was  collected through questionnaires. Results: The paper derives its findings from observations &  questionnaires & feedback forms collected from women professionals of the hospitality industry is  that the women are facing is gender discrimination. Conclusion : The society should undersatnd  that today's women are countributing to the ecomomic development of the country and not look the  upon as an inferior creature.
Keywords: Discrimination; Family; Hospitality; Profession